Suicides in the Bernese mountains - Elena Schoch; Christian Mikutta; Eva Allenbach; Joel Notz; Thomas J. Müller; Christian Jackowski; Corinna Ariane Schön (Sports Psychiatry)
Abstract: Introduction: Jumping/falling from high structures is a common form of suicide. Mostly, these suicides occur on artificial structures. However, there are also natural formations which are used for committing suicide. It was the aim of this study to investigate the use of mountains and other natural rock formations for the means of suicide. Methods: The files of the investigations of mountain deaths from 2002 to 2016 commissioned by the public prosecutor’s office of the canton of Bern, Switzerland, or carried out by the Institute of Forensic Medicine in Bern itself, were evaluated retrospectively regarding the existence of suicides within alpine environment. Results: 20 cases were analyzed concerning various parameters such as method, age, gender and mental diagnoses. A mountain suicide occurred with a ratio of 1 to 69. The gender difference was more pronounced with 80% being male victims. Discussion: Suicide is rare in the mountains. Jumping/falling from heights was the most common manner of suicide. Most of those affected were male and a significant proportion had a psychiatric diagnosis.